Wajahku Cerah dan Glowing: Efektivitas Afirmasi Positif untuk Mengurangi Tingkat Stres - Rida Yanna Primanita; Puput Nofia Rahma (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to examine the effectiveness of positive affirmations in reducing stress levels and their impact on physical conditions, particularly among university students. The research employed a quasi-experimental method with a One Group Pretest-Posttest design. The sample consisted of 7 psychology students from Universitas Negeri Padang (class of 2024), selected using a purposive sampling technique. The intervention involved performing positive affirmations independently for 30 days. The results showed a significant reduction in stress levels after the intervention, as evidenced by pretest and posttest scores. This stress reduction also positively affected physical conditions, such as brighter and healthier facial skin. The findings align with previous research, highlighting that positive affirmations can alleviate stress by enhancing positive emotions and stimulating the production of anti-stress hormones. Positive affirmations offer a practical method for improving mental and physical well-being, particularly for students.